2020
DOI: 10.33860/jik.v14i1.85
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Deep Back Massage dan Massage Endorphin terhadap Intensitas Nyeri Kala I Fase Aktif di BPM Setia

Abstract: The preferred delivery for every pregnant woman is labor with minimal pain. Labor Pain is caused by the process of contraction of the uterus in an effort to remove the fruit of pregnancy. One technique without drugs or non-pharmacological that can be to provide comfort to the mother in the face of labor is massage. The purpose of this study was to determine the effectiveness of the Deep Back Massage and Endorphin Massage methods on the intensity of pain in the active phase I at BPM Setia. This research was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Manusia melakukan berbagai cara untuk mengurangi bahkan menghilangkan rasa sakit atau nyeri karena berbagai sebab. Untuk nyeri persalinan, metode farmakologi atau menggunakan (obat-obatan) maupun non-farmakologi (melalui teknik non obat-obatan misalnya pijatan, sentuhan ataupun mendengarkan music) banyak digunakan (Dewie & Kaparang, 2020). Adapula yang menyebutkan jenis terapi non-farmakologi terdiri dari distraksi, relaksasi, kompres dan massage (F. B. Faridah dkk., 2017).…”
Section: Pendahuluanunclassified
“…Manusia melakukan berbagai cara untuk mengurangi bahkan menghilangkan rasa sakit atau nyeri karena berbagai sebab. Untuk nyeri persalinan, metode farmakologi atau menggunakan (obat-obatan) maupun non-farmakologi (melalui teknik non obat-obatan misalnya pijatan, sentuhan ataupun mendengarkan music) banyak digunakan (Dewie & Kaparang, 2020). Adapula yang menyebutkan jenis terapi non-farmakologi terdiri dari distraksi, relaksasi, kompres dan massage (F. B. Faridah dkk., 2017).…”
Section: Pendahuluanunclassified
“…By doing deep back massage for 30 minutes in the treatment group, this study showed an increase in endorphin above the average normal value after massage was performed on the backs of mothers in the latent phase of the first stage of labor who experienced labor pain. Whereas in the control group there was no increase in endorphin and the average endorphin levels were at normal values, some were even below normal values (Dewie & Kaparang, 2020) When the mother is being touched, namely back deep massage and pain is stimulated together with the sensation of touch walking to the mind mother and closing the gates in the brain, limiting the amount of pain felt in the mother's mind. Massage given regularly with breathing exercises during contractions is used to distract the mother from going into labor during contractions.…”
Section: Discussionmentioning
confidence: 91%
“…Based on Table 1, it can be interpreted that there is a significant difference in labor pain after being given endorphin massage intervention and back deep massage, this can be seen from the significance of <0.0001, less than 0.05. Research in Lampung concluded that it is true that Endorphin massage has an effect on reducing the pain felt by mothers in labor so that it can provide comfort and a sense of security during the labor process (Dewie & Kaparang, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Begitu juga dengan tekanan darah. 9 Pada dasarnya, nyeri pada saat persalinan yang dialami ibu melahirkan disebabkan adanya kontraksi dan pembukaan servik yang semakin besar. Selain faktor tersebut, rasa kecemasan dan ketakutan yang dialami ibu dalam proses melahirkan juga memberikan pengaruh besar timbulnya rasa nyeri 2 Teknik sentuhan ringan juga membantu menormalkan denyut jantung dan tekanan darah.…”
Section: Jurnal Ilmu Kedokteran Dan Kesehatan Indonesiaunclassified